Response biases in the divided visual field lexical decision task: A diffusion model account. - Tomkins, Blaine; Perea, Manuel; Virtue, Sandra; Gomez, Pablo (Visual Cognition, 2025)
The diffusion model (Ratcliff et al., 2004) has been used to account for data patterns in the lexical decision task. However, no published studies have examined whether the diffusion model can account for hemispheric differences and response biases in the divided visual field-lexical decision task (DVF-LDT). Participants completed the DVF-LDT using different response mapping assignments. A left hemisphere advantage was observed for word and nonword stimuli; however, this advantage was significantly larger when response keys were location-congruent with the stimulus. Importantly, these effects were unrelated to word frequency, suggesting the left hemisphere advantage for word processing occurs at the pre-lexical stage. Modelling results showed the diffusion model can adequately fit participant data in the DVF-LDT, including response biases. These findings demonstrate that decisional, hemispheric, and motor processes all interact during word recognition tasks and vertical orientation of response keys is insufficient to eliminate response biases in the DVF-LDT.